Safety and efficacy profile of an indigenous developed CHARAK DDDR 747R dual-chamber rate-responsive pacemaker: A prospective study from a tertiary care center in North India - Yash Paul Sharma; Akash Batta; Saurabh Mehrotra; Prashant Panda; Surendra Sethi (Heart India, 2022)
Aim: The purpose of this study was to assess the safety and performance of the domestically manufactured Charak DDDR 747R (Pacetronix Ltd, Indore, India) pacemaker device. Materials and Methods: This was a prospective, controlled, single-center study conducted between March 2016 and August 2017. Eligible patients were implanted with a Charak DDDR 747R pacemaker with parameters set as specified on the packaging material unless otherwise advised by the physician. Patients were evaluated before discharge and at the 18-month follow-up. Data such as patient age, gender, and medical history were collected to determine patient eligibility for study participation, monitoring of study progress, and data analysis. Results: A total of 35 patients were analyzed. Males comprised 45.7% and females comprised 54.3% of patients. The average pacing threshold was threshold (atrium) was 1.05 V and the average pacing threshold (ventricle) was 1.07 V. The average impedance (atrium) was 641.09 Ω and the average impedance (ventricle) was 719.31 Ω. No serious adverse events were documented during the follow-up. One death occurred; however, this was not device-related. Conclusions: As per study findings, the Charak DDDR 747R, an indigenous pacemaker, is safe and effective in the Indian population. Durable lead parameters were obtained during the study which remained stable over time referring the same. Future larger studies are needed to confirm the preliminary data obtained from our study.